2009
DOI: 10.1002/cm.20339
|View full text |Cite
|
Sign up to set email alerts
|

Modulating α‐actinin‐4 dynamics in podocytes

Abstract: Podocytes are epithelial cells that line the outer aspect of renal blood vessels and provide a platform for the kidney's filtering apparatus, the slit diaphragm. Mutations in alpha-actinin-4, an actin bundling protein highly expressed in podocytes, result in increased affinity for actin and cause a familial form of focal segmental glomerulosclerosis. We hypothesized that such gain-of-affinity mutations would override alpha-actinin-4's sensitivity to regulatory factors such as calcium (acting via two EF-hand mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 20 publications
2
16
1
Order By: Relevance
“…This also strongly supports the contention that ACTN4 differs from ACTN1 in integrating the membrane with the actin cytoskeleton possibly by bridging between actin and phosphoinositides on the membrane (13,17,38) rather than simply bundling actin filaments. Further studies are needed to decipher the molecular mechanisms by which the expression of ACTN4 but not ACTN1 is elevated in melanoma and the increase of ACTN4 expression regulates the metastasis and invasiveness.…”
Section: Discussionsupporting
confidence: 79%
“…This also strongly supports the contention that ACTN4 differs from ACTN1 in integrating the membrane with the actin cytoskeleton possibly by bridging between actin and phosphoinositides on the membrane (13,17,38) rather than simply bundling actin filaments. Further studies are needed to decipher the molecular mechanisms by which the expression of ACTN4 but not ACTN1 is elevated in melanoma and the increase of ACTN4 expression regulates the metastasis and invasiveness.…”
Section: Discussionsupporting
confidence: 79%
“…For α -actinin-4, the phosphoinositide-binding site is within the CH2 domain. In contrast to findings for α -actinin-1, our studies showed that phosphoinositides increase the interaction of α -actinin-4 with F-actin [19]. Phosphorylation of α -actinin-1 has been reported in activated platelets [20].…”
Section: Role Of α-Actinin-4 In Cell Biologycontrasting
confidence: 84%
“…Another consideration is that SLK alters the phosphorylation and function of α-actinin-4, including its actin-binding properties. It has been demonstrated that adoption of an "open" conformation of α-actinin-4 by mutational disruption of the CH2 domain increases its affinity for actin [42]. Since SLK can bind to the N-terminus of α-actinin-4, which contains the CH2 domain, SLK may inhibit formation of the open conformation of α-actinin-4, and negatively regulate actin binding.…”
Section: Discussionmentioning
confidence: 98%